A kind and just parent: the children of juvenile court - Ayers, William (Beacon Pr., 1997)
Most people know juvenile offenders only from daily headlines, and the images portrayed by the media are extreme and violent: predators and even "superpredators." Distorted and incomplete, these pictures shape the way Americans think and feel about city kids, poor kids, children of color. A Kind and Just Parent gives us a transformative view of kids caught up in the justice system that we could never get from nightly news and newspaper stories. William Ayers has spent five years as teacher and observer in Chicago's Juvenile Court prison, the nation's first and largest institution of juvenile justice, founded by legendary reformer Jane Addams to act as a "kind and just parent" for kids in need. Today, immensely confused and confusing, it serves as a perfect microcosm of the way American justice deals with children.